Behavioral Modernity in Retrospect. - Davies, Stephen (Topoi: An International Review of Philosophy, 2021)
This paper reviews the debate about behavioral modernity in our species, listing counterexamples to the thesis that there was a dramatic change to the minds of Cro-Magnon sapiens in Europe in the Upper Paleolithic. It is argued that we were probably behaviorally modern from about 150,000 years ago, and that aspects of this mentality were apparent in developments in tool technologies and hunting practices across the prior Homo lineage. Key behaviors expressive of behavioral modernity include practical reasoning about the past and future and role-differentiated rights-based cooperation, which are more obvious in their effects than is the vague but much-used notion of symbolic thinking. Behavioral modernity leads to technological innovation but is not sufficient to maintain such innovations in face of population loss and environmental instability, which along with the vagaries of preservation explains why the archaeological record of behavioral modernity in our species is patchy until the Upper Paleolithic.